The effect of aromatherapy on labor Pain relief: a systematic review of clinical trials - Ashraf Ghiasi; Maryam Hasani; Leila Mollaahmadi; Mozhgan Hashemzadeh; Arezoo Haseli (Mashhad University of Medical Sciences, 2017)
Introduction: Alleviating labor pain has always been one of the most important issues in midwifery practice. Nowadays, non-pharmacological pain relief methods such as aromatherapy are considered due to low side effects. This study was performed with aim to review the studies which evaluated the effect of aromatherapy on relief of labor pain. Methods: In this review study, electronic databases including: SID, Iranmedex, Magiran, IranDoc, Cochrane Library, MEDLINE/PubMed, Scopus and Google Scholar were searched with the keywords of aromatherapy, labor pain and clinical trial up to November 9, 2016. Search was limited based on English or/and Persian articles. The quality of studies was assessed using the Cochrane "risk of bias" tool. The results were reported qualitatively. Results: Of 456 articles which were found in the initial search, 24 randomized trials (3414 participants) were selected for systematic review. The studies were conducted in Iran, India, Egypt, Korea, Italy and New Zealand. The used essence were lavender in 11 articles, rose in 6 articles, common sage in 3 articles, geranium in 3 articles, jasmine in 3 articles, chamomile in 2 articles, peppermint in 2 articles, bitter orange in 1 article, mandarin in 1 article, orange in 1 article, pink in 1 article, ginger in 1 article, lemongrass in 1 article and frankincense in 1 article. Most of the studies showed the positive effects of aromatherapy on labor pain relief. Conclusion: Available data demonstrate that aromatherapy can be an effective intervention for alleviation of labor pain, but more studies with strong methodology are needed to achieve more rigorous evidence.